Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.1002/sia.740020305
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interface analysis in polymer technology: A review

Abstract: Surface analysis methods like ESCA, AES, SIMS and ISS can provide valuable information on the structure and composition of polymer surfaces. Examples of application are the investigation of surface changes, such as the effects of weathering, etching and corona treatments, and the detection of surface deposits consisting of materials like antistatic agents, lubricants and exuded constituents. Because of their high surface sensitivity and ability to differentiate between surface and bulk phenomena, surface analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

1981
1981
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 23 publications
(4 reference statements)
0
14
0
2
Order By: Relevance
“…In the repeat unit of PEEK this ratio is 6.33. This agreement is good in that C:O ratios measured by XPS frequently differ from calculated values [16] and quantitative accuracy of the analysis of polymer surfaces is generally in the region 15-20%. The presence of residual degreasing solvent was considered unlikely because of the reported resistance of PEEK to acetone [17].…”
Section: Untreated Surfacesmentioning
confidence: 57%
“…In the repeat unit of PEEK this ratio is 6.33. This agreement is good in that C:O ratios measured by XPS frequently differ from calculated values [16] and quantitative accuracy of the analysis of polymer surfaces is generally in the region 15-20%. The presence of residual degreasing solvent was considered unlikely because of the reported resistance of PEEK to acetone [17].…”
Section: Untreated Surfacesmentioning
confidence: 57%
“…Although each Cls peak was somewhat broad, which may have been due to locally different charging, the C1~ peak shape analysis could be easily carried out. In general, XPS measurement can yield information for a polymer sample to a depth of 50-100 A [16,17]. The peak shape analysis indicated that Ca:cb:c c was 3.…”
Section: Oh Imentioning
confidence: 99%
“…An excellent introduction to the common features observed in electron spectra of non metallic surfaces and a simple discussion of the physical processes giving rise to these features is included in the review article by Holm and Storp (7).…”
Section: Introduction To Core Electron Spectra Of Polymeric Materialsmentioning
confidence: 99%